Isotonic Glycerol and Sodium Hyaluronate Containing Artificial Tear Decreases Conjunctivochalasis after One and Three Months: A Self-Controlled, Unmasked Study. - Huba J Kiss; János Németh (PLoS ONE, 2015)
Dry eye complaints are ranked as the most frequent symptoms of patients visiting ophthalmologists. Conjunctivochalasis is a common dry eye disorder, which can cause an unstable tear film and ocular discomfort. The severe conjunctivochalasis characterized by high LId-Parallel COnjunctival Folds (LIPCOF) degree usually requires surgical intervention, where a conservative therapy would be highly desirable. Here we examined the efficacy of a preservative-free, inorganic salt-free unit-dose artificial tear, called Conheal containing isotonic glycerol and 0.015% sodium hyaluronate in a prospective, unmasked, self-controlled study involving 20 patients. The regular use of the glycerol/hyaluronate artificial tear in three months caused a significant improvement in the recorded parameters. Conjunctivochalasis decreased from a mean LIPCOF degree of 2.9 ± 0.4 on both eyes to 1.4 ± 0.6 on the right (median decrease of -2 points, 95% CI from -2.0 to -1.0), and to 1.4 ± 0.7 on the left eye (median decrease of -1 points, 95% CI from -2.0 to -1.0) (p<0.001 for both sides). The tear film breakup time (TFBUT) lengthened from 4.8 ± 1.9 seconds on both eyes to 5.9 ± 2.3 seconds (mean increase of 1.1 seconds, 95% CI from 0.2 to 2.0) and 5.7 ± 1.8 seconds (mean increase of 0.9 seconds, 95% CI from 0.3 to 1.5) on the right and left eyes, respectively (p(right eyes) = 0.020, p(left eyes) = 0.004). The corneal lissamine staining (Oxford Scheme grade) was reduced from 1.3 ± 0.6 on the right and 1.4 ± 0.6 on the left eye significantly (p<0.001) to 0.3 ± 0.4 and 0.2 ± 0.4 on the right and the left eyes. The Ocular Surface Disease Index (OSDI) questionnaire score indicating the subjective complaints of the patients also decreased from a mean value of 36.2 ± 25.3 to 15.6 ± 16.7 (p<0.001). In this study, the artificial tear, Conheal decreased the grade of the conjunctivochalasis significantly after one month of regular use already, from the LIPCOF degree 3, considered as indication of conjunctival surgery, to a LIPCOF degree 2 or lower requiring a conservative therapy. Our results raise the possibility that vision-related quality of life can be significantly improved by conservative therapies even in severe conjunctivochalasis.Controlled-Trials.com ISRCTN81112701 http://www.isrctn.com/ISRCTN81112701.